2006
DOI: 10.1111/j.1742-4658.2006.05248.x
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for the recognition of complex‐type biantennary oligosaccharides by Pterocarpus angolensis lectin

Abstract: Lectins (or lectin domains) represent a specific class of carbohydrate binding proteins distinct from enzymes and antibodies. Different lectin families are found in a wide range of organisms including viruses, bacteria, plants and animals. Their biological activities are diverse and include roles in the innate immunity, bacterial and viral infection, sorting and trafficking of glycoproteins, development and differentiation as well as defense mechanisms in plants [1].The lectins from legume plants belong to one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
14
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 46 publications
2
14
0
Order By: Relevance
“…The carbohydrate-binding site of subunit A is involved in crystal packing and therefore limits the conformations that are accessible to the bound carbohydrate. After the desoaking step (see ''Materials and Methods''), a molecule of Mana(1-3)Man remains bound (Loris et al, 2005), but in a number of cases this can still be substituted by a different carbohydrate ligand if the concentration of the replacing ligand is sufficiently high (Loris et al, 2003(Loris et al, , 2004Buts et al, 2006). The interactions and carbohydrate conformations observed in this binding site then have to be interpreted as situations that are possible in solution, but not necessarily reflecting the dominant one.…”
Section: Overall Structurementioning
confidence: 99%
See 3 more Smart Citations
“…The carbohydrate-binding site of subunit A is involved in crystal packing and therefore limits the conformations that are accessible to the bound carbohydrate. After the desoaking step (see ''Materials and Methods''), a molecule of Mana(1-3)Man remains bound (Loris et al, 2005), but in a number of cases this can still be substituted by a different carbohydrate ligand if the concentration of the replacing ligand is sufficiently high (Loris et al, 2003(Loris et al, , 2004Buts et al, 2006). The interactions and carbohydrate conformations observed in this binding site then have to be interpreted as situations that are possible in solution, but not necessarily reflecting the dominant one.…”
Section: Overall Structurementioning
confidence: 99%
“…To produce complexes with high Man oligosaccharides, these crystals were first desoaked by transferring them to artificial mother liquor devoid of sugar (100 mM Na-cacodylate pH 6.5, 200 mM Ca-acetate, 20% [w/v] PEG-8000) for (Loris et al, 2005;Buts et al, 2006). Desoaked crystals were then transferred to 1 mL drops containing 20 mg of the desired sugar.…”
Section: Crystallization and Data Collectionmentioning
confidence: 99%
See 2 more Smart Citations
“…the agglutinin from Pterocarpus angolensis seed (PAL). 4 Crystallography and thermodynamic studies demonstrated high affinity for both oligomannose N-glycans and for biantennary complex type, correlated with the presence of an unusually extended binding region close to the primary binding site (17)(18)(19)(20).…”
mentioning
confidence: 99%